Viviparity in snakes - Cigler, Pia (Slovenian veterinary research, 2023)
Viviparity is an important reproductive mode in reptiles from an evolutionary perspective. Viviparous reproduction is associated with certain physiological changes, probably in response to inadequate environmental conditions for egg development. Unlike in oviparous species, embryos remain and develop in the oviduct until birth. In order for the developing embryo to exchange respiratory gasses, water, and food, a placenta is required, which consists of fetal membranes that interact with the maternal oviduct. About 20% of squamates (snakes and lizards) are viviparous, but the morphology of the snake placenta has been studied only in the subfamilies Thamnophiinae and Hydrophiinae. Our objective was to study the structure of the placental layers and fetus in situ in the maternal oviduct of a 6-year-old Emerald tree boa (Corallus caninus). Five fertilized and three unfertilized slugs were found in the uterus during post mortem examination. The average mass of the slug with the fetus (48 mm length x 26 width) was 55-65 g and that of the unfertilized slug was 15-35 g. The fetal membranes and two fetuses were examined by light microscopy. Multiple projections of the tissue samples were made and cut into 5 µm thick paraffin tissue sections, which were stained with Haematoxylin-eosin, Toluidine blue, Goldner’s Trichrome and assessed immunohistochemically with monoclonal antibodies for cytokeratin. The morphology of the fetal membranes was described and found to have an anatomy similar to that of most squamates: a type I allantoplacenta. Th structure of the oviduct and of the fertilized and unfertilized slug was described. This case report provides a better understanding of placental morphology in boids and expands the spectrum of viviparous squamate species described.
Keywords: Histology; Immunohistochemistry; Placenta; Snakes